Girl in the woods : a memoir - Matis, Aspen (HarperCollins Publishers, 2015)
An exhilarating true-life adventure of hiking from Mexico to Canada--a coming of age story, a survival story, and a triumphant story of overcoming emotional devastation. On her second night of college, Aspen was raped by a fellow student. Overprotected by her parents who discouraged her from telling of the attack, Aspen was confused and ashamed. Dealing with a problem that has sadly become all too common on college campuses around the country, she stumbled through her first semester--a challenging time made even harder by the coldness of her college's "conflict mediation" process.